Occupational hazards and health care seeking behavior of fishermen - Noman, Mohammad Abdulla Al; Sharmin, Tarana; Shoshi, Fatema Kabir; Sanjida, -; Anee, Kanij Fatima; Hossain, Md Belal; Islam, Md Nazrul; Khan, Md Shafiqul Islam (Asian Journal of Medical and Biological Research, 2020)
About millions of households depend on fishing for livelihood though it is associated with different types of hazards. Working time does not allow fishermen to get health care for hazards from facilities. Data on occupational hazards and health care seeking is inconclusive in Bangladesh. This study was undertaken to assess the occupational hazards, associated factors and health seeking of fisherman. A cross sectional study involving 300 fishermen conducted from some selected communities of Patuakhali and Vhola districts from January to June, 2018. A pretested questionnaire used to collect information on socio-demography, occupational detail, types of hazards and health seeking behavior of fishermen. The results revealed that 69 faced different occupational problems during last 6 months. Participants suffered mainly from skin disease (31.7%), musculoskeletal pain (29.7%) and fever (24.3%). Age and duration of profession identified were associated (P= <.001) with occupational hazards. Only 7.3% respondents went to facilities to get health care. Nearly one-third of fishermen (31%) took medicine by their own idea. Fishermen who seek care from facilities are low than affected with health hazards. Establishing facilities near major fish landings may improve health care seeking in this study area. Asian J. Med. Biol. Res. March 2020, 6(1): 38-43